Study of Characteristics Curves Top-Gated Graphene FET Using SILVACO TCAD - Muhammad Johirul Islam; Rifat Sami; Md. Shafiqul Islam; Md. Iqbal Bahar Chowdhury (Journal of Electronic Design Engineering, 2017)
This work presents a SILVACO TCAD based fabrication and device simulation of a topgated graphene field-effect transistor. Effects of channel length and channel doping concentrations on the characteristics curves (transfer and output characteristics) of the GFET are also investigated and analyzed physically to obtain more physical insight.